Intention towards vegetarian diet in Malaysia as a concern of healthy eating lifestyle - Islam, Md. Jahirul (2018)
Human health can be described as an individual’s quality of life and the impacts of such living pattern on the development of the individual’s social and economic aspects. One of the most effective ways of ensuring healthy living is the adoption of vegetarian foods. Vegetarian foods play an important role in healthy eating as they offer several health benefits and provide protection against numerous diseases. Despite all the advantages, the development of green food markets and the consumers’ interest in the vegetarian culture are still below the satisfactory level in Malaysia. Thus, it becomes necessary to examine the consumers’ perception, attitude and intention towards vegetarian food consumption with regards to healthy eating lifestyle. In total, 1000 respondents were interviewed via structured questionnaire. The result of the factor analysis revealed that most of the factor loadings are above 0.60 which is considered acceptable. As hypothesized in the study, the result of the first regression analysis showed that perceived health status, perceived control of health and perceived benefit of health promoting behavior have positive relationship with attitude. The perceived barrier to health promoting behavior is also positive but not significant. The result of the second regression analysis revealed that attitude, subjective norm, and perceived behavioral control have significant positive relationship with consumers’ intention to consume vegetarian foods. The result of the study showed that consumers have positive perception and attitude towards vegetarian food which can be explored to improve its adoption with regards to healthy eating lifestyle. Thus, efforts need to be intensified in the form of increased campaigns by all stockholders such as the food industry, government agencies, health bodies, and consumer groups.